The Experience of Ethnic Identi fi cation on Intermarriages of Koreans in Japan (Journal of Oriental Studies, 2016)
Based on the theory of ethnic identification of the author in this paper has researched particularities of ethnicidenti fication of the Korean diaspora in Japan: the case of inter-ethnic marriages.
Keywords: ethnic identity; mixed marriages